Outcomes of Chimney Technique for Preservation of the Left Subclavian Artery in Type B Aortic Dissection. (March 2019) - Ding, Huanyu; Liu, Yuan; Xie, Nianjin; Fan, Ruixin; Luo, Songyuan; Huang, Wenhui; Li, Jie; Zhu, Yi; Hu, Binquan; Xue, Ling; Luo, Jianfang
Abstract : Objective: To report outcomes of the chimney technique for preservation of the left subclavian artery (LSA) in patients with type B aortic dissection (TBAD). Methods: A retrospective analysis was performed of a prospectively maintained database from August 2012 to October 2017. Primary endpoints were 30 day and overall mortality. Secondary endpoints were technical success, type Ia endoleak, chimney stent occlusion, aortic rupture, stroke, spinal cord ischaemia, and re-intervention rate. Results: A total of 159 patients (mean age 54 ± 11 years; 141 men) with TBAD were treated using the chimney technique for LSA revascularisation. Acute, subacute, and chronic TBAD accounted for 64%, 28%, and 8% of cases, respectively. One hundred and six cases (67%) were complicated TBAD. One hundred and fifty-six patients (98%) were treated electively, while three (2%) were treated urgently because of intestinal or lower extremity ischaemia. The 30 day mortality and morbidity rates were 2% (3/159) and 4% (7/159), respectively. The technical success rate was 81% (129/159) and immediate type Ia endoleak occurred in 30 (19%) patients. Three major strokes, two spinal cord ischaemia and one aortic rupture, occurred early on. During a mean follow up of 23 ± 16 months (range 1–65 months), three more patients died: from aortic rupture, cerebral haemorrhage, and rectal cancer, respectively. Chimney stent occlusions were observed in four patients and all these chimney stents were self expanding. During follow up, two major strokes, one late type Ia endoleak and one re-intervention, occurred. According to the Kaplan–Meier curve, the estimated one and three year survival rates were 98.1 ± 1.1% and 94.4 ± 2.4%, respectively. Conclusion: Short and mid-term outcomes in the present study demonstrate that the chimney technique is safe and feasible for preservation of the LSA in patients with TBAD, but the durability of chimney stent needs to be evaluated carefully and immediate type Ia endoleak is a concern.